BalOnSe: Ballet ontology for annotating and searching video performances - El Raheb, K.; Papapetrou, N.; Katifori, V.; Ioannidis, Y. (Proceedings of the 3rd International Symposium on Movement and Computing, 2016)
In this paper we present BalOnSe (named after the ballet step balance), an ontology-based web interface that allows the user to annotate classical ballet videos, with a hierarchical domain specific vocabulary and provides an archival system for videos of dance. The interface integrates a hierarchical vocabulary based on classical ballet syllabus terminology (Ballet.owl) implemented as an OWL-2 ontology. BalOnSe supports the search and browsing of the multimedia content using metadata (title, dancer featured, etc.), and also implements the functionality of "searching by movement concepts", i.e., filtering the videos that are associated with particular required terms of the vocabulary, based on previous submitted annotations. In the paper, we present the ballet.owl ontology, and its structure, explaining the conceptual modeling decisions. We highlight the main functionality of the system and finally, we present how the manual ontology guided annotation allows the user to search the content through the vocabularies and also view statistics in the form of tag clouds.